Neighbourhood Policing and Social Cleansing of Crime in Oke-Ogun Area of Oyo State, Nigeria - Folasade O, ADIGUN (2019)
The paper assessed neighbourhood policing and social cleansing of crime in Oke-Ogun area of Oyo State with a view to examining spatial variation in response to crime in the area. Both primary and secondary data were employed. The total households of urban and rural settlements as identified in Oke-Ogun area of Oyo State were 44,421 and 175,568 respectively The sample frame constituted all households in the study area, and five out of 1000 of all the 219,989 total households which approximately amount to 1100 households constituted the sample size, Random sampling was employed in hierarchical selection of 50/00 of the total households in each settlement type, and a total number of 1100 copies of questionnaires were randomly administered Descriptive statistics such as percentage and Chi-Square were used to present summary of findings. Findings revealed that higher order security consciousness was displayed in urban area with an insubstantial proportion of households surveyed (13.2%) having no organisation responsible for security in their neighbourhood compared with 22.4% in the rural settlements. At aggregation level, 52% of all respondents in Oke-Ogun agreed with the adequacy of policing out of which 13.6% said that the policing was very adequate and 38.4% said that it was adequate while 48% of all respondents were at variance with the adequacy of policing. The households (49.0%) in the rural areas were cynical about adequacy of policing, while out of 49.0%, 28.9% said that policing was inadequate and 20.1% said that policing was very inadequate. The chi-square performed across settlement types at (P<0.05) indicates that the difference in adequacy of policing was significant. The implication of this is that there is a significant difference between perception of adequacy of policing by households and the settlement types in Oke-Ogun. Households also held view that Police in Oke-Ogun did not give a prompt response expected in situations of distress call. Response to unwillingness to give prompt response to distress call by Police was on top gear in rural settlements. About 39% of all respondents in rural areas said that Police gave prompt response needed to distress call compared to 41.7% in urban areas of Oke-Ogun. For social cleansing job provision for the unemployed was ranked first by the residents among alternatives for keeping neighbourhood safe, followed by imposition of fine on offender. Jailing of offender was ranked third and equip vigilant groups was ranked fourth Improved infrastructure was ranked fifth among several options. The chi-square analysis performed (P<0.05) indicated that the difference in households’ preference for means of keeping neighbourhood safe across settlement type was significant. The study concluded that response to crime in the area varied spatially. Keywords: Crime, Neighbourhood, Policing, Social cleansing DOI: 10.7176/JCSD/51-06 Publication date:September 30th 201